2000
DOI: 10.1038/35046619
|View full text |Cite
|
Sign up to set email alerts
|

A yeast DNA J protein required for uncoating of clathrin-coated vesicles in vivo

Abstract: Clathrin-coated vesicles mediate diverse processes such as nutrient uptake, downregulation of hormone receptors, formation of synaptic vesicles, virus entry, and transport of biosynthetic proteins to lysosomes. Cycles of coat assembly and disassembly are integral features of clathrin-mediated vesicular transport (Fig. 1a). Coat assembly involves recruitment of clathrin triskelia, adaptor complexes and other factors that influence coat assembly, cargo sequestration, membrane invagination and scission (Fig. 1a).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
118
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 32 publications
9
118
0
Order By: Relevance
“…Furthermore, a recent mechanistic study of individual baskets has revealed a cooperative uncoating mechanism under single turnover conditions, with Hsc70 and auxilin prebound to baskets tethered to a coverslip (20). Although genetic evidence from S. cerevisiae has confirmed that the Hsc70 ortholog, Ssa1p, and the auxilin ortholog, Swa2p, are necessary for clathrin uncoating (4,5,22), it has not been determined whether these proteins are sufficient for yeast clathrin coat disassembly in a reconstituted system. To examine the mechanism of clathrin uncoating in yeast, we analyzed the single-particle dynamics of clathrin coat disassembly, in free solution, reconstituted from purified components.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, a recent mechanistic study of individual baskets has revealed a cooperative uncoating mechanism under single turnover conditions, with Hsc70 and auxilin prebound to baskets tethered to a coverslip (20). Although genetic evidence from S. cerevisiae has confirmed that the Hsc70 ortholog, Ssa1p, and the auxilin ortholog, Swa2p, are necessary for clathrin uncoating (4,5,22), it has not been determined whether these proteins are sufficient for yeast clathrin coat disassembly in a reconstituted system. To examine the mechanism of clathrin uncoating in yeast, we analyzed the single-particle dynamics of clathrin coat disassembly, in free solution, reconstituted from purified components.…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical research using purified neuronal proteins has demonstrated that clathrin coats (hereafter referred to as "baskets," when membrane is absent), Hsc70, auxilin, and ATP comprise the minimal system to reconstitute clathrin uncoating in vitro (4,8,10,14). Furthermore, a recent mechanistic study of individual baskets has revealed a cooperative uncoating mechanism under single turnover conditions, with Hsc70 and auxilin prebound to baskets tethered to a coverslip (20).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations